SERVICE PHONE CALL OPENINGS IN ITALIAN AS A SECOND LANGUAGE TEXTBOOKS (ItalianoLinguadue, 2019)
The present paper investigates how textbooks for learners of Italian offer samples of service telephone conversations, especially in their opening sequences, in terms of what data they use and how they present it to the learner. Textbooks are also compared to the existing conversational studies which focus on native speakers’ routines and practices. Back in 2002, Wong reported a mismatch between textbooks and naturally occurring language, which had implications for teachers and writers of teaching materials, especially if, as it is currently common practice for developing teaching materials, these are «marketed as offering authentic, natural language, or language which is true to life». The opening sequence of service telephone calls was therefore observed in the textbook extracts, looking at the presence of the interactional moves characteristic of this kind of conversation, and also at the alternation between the Caller and Operator, in terms of sequential order of the opening moves and their combination in taking turns in the conversations. Results showed that textbook Operators seemed to show convergence with real phone calls in presenting the prototypical formats and their relative frequency, whereas Callers’ first turns displayed many more differences. Both similarities and differences are discussed in detail. Practical implications are also raised with concern to textbook authors and the development of teaching materials, as well as issues related to language learning and teaching. Conversazioni telefoniche di servizio nei libri di testo di italiano L2Il presente contributo indaga come i libri di testo per studenti di italiano L2 offrono esempi di conversazioni telefoniche di servizio analizzando, in particolare, le sequenze di apertura, quali dati usano e come li presentano allo studente. I libri di testo sono inoltre messi a confronto con gli studi conversazionali esistenti che si occupano delle routine e delle pratiche dei madrelingua. Nel 2002, lo studio di Wong mise in evidenza come la discrepanza che esiste tra i libri di testo e il linguaggio naturale abbia implicazioni per gli insegnanti e gli estensori di materiale didattico, specialmente se questo è commercializzato come autentico e cioè presenti espressioni reali della lingua utili per la vita. Sono state quindi estratte dai libri di testo sequenze di apertura delle chiamate telefoniche di servizio osservando la presenza delle mosse interattive caratteristiche di questo tipo di conversazione e, in particolare, la composizione dei primi turni di parola tra chi chiama e l’operatore che risponde, l’ordine sequenziale delle mosse di apertura e la loro combinazione nel turno di parola. I risultati evidenziano come i libri di testo sembrino mostrare convergenza con le telefonate reali nel presentare i formati prototipici e la loro relativa frequenza e come i primi turni dei callers risultino invece molto diversi da quelli reali. Queste somiglianze e differenze vengono analizzate in dettaglio. Vengono infine discusse alcune implicazioni pratiche per gli autori di libri di testo e per la stesura di materiale didattico per l’apprendimento e l’insegnamento delle lingue.